Investigations into Deformation Characteristics during Open-Die Forging of SiCp Reinforced Aluminium Metal Matrix Composites. (10th October 2013) - Verma, Deep; Chandrasekhar, P.; Singh, S.; Kar, S.
Abstract : The deformation characteristics during open-die forging of silicon carbide particulate reinforced aluminium metal matrix composites (SiCp AMC) at cold conditions are investigated. The material was fabricated by liquid stir casting method in which preheated SiC particles were mixed with molten LM6 aluminium casting alloy and casted in the silicon mould. Finally, preforms obtained were machined in required dimensions. Two separate cases of deformation, that is, open-die forging of solid disc and solid rectangular preforms, were considered. Both upper bound theoretical analysis and experimental investigations were performed followed by finite element simulation using DEFORM, considering composite interfacial friction law, barreling of preform vertical sides, and inertia effects, that is, effect of die velocity on various deformation characteristics like effective stress, strain, strain rate, forging load, energy dissipations, and height reduction. Results have been presented graphically and critically investigated to evaluate the concurrence among theoretical, experimental, and finite element based computational findings.